Superalloys 2012 2012
DOI: 10.1002/9781118516430.ch95
|View full text |Cite
|
Sign up to set email alerts
|

Oxidation and the Effects of High Temperature Exposures on Notched Fatigue Life of an Advanced Powder Metallurgy Disk Superalloy

Abstract: Oxidation and the effects of high temperature exposures on notched fatigue life were considered for a powder metallurgy processed supersolvus heat-treated ME3 disk superalloy. The isothermal static oxidation response at 704 °C, 760 °C, and 815 °C was consistent with other chromia forming nickel-based superalloys: a TiO 2 -Cr 2 O 3 external oxide formed with a branched Al 2 O 3 internal subscale that extended into a recrystallized γ'-dissolution layer. These surface changes can potentially impact disk durabilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
36
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(42 citation statements)
references
References 10 publications
(4 reference statements)
2
36
1
Order By: Relevance
“…[10][11][12][13][14] Energy-dispersive x-ray analyses showed that the overall oxide morphology from the external scale to internal oxides of Cr 2 O 3 /TiO 2 in the outer scale to Al 2 O 3 internally agrees with the expected thermodynamic behavior; however, and in contrast to the thermodynamic predictions, the alloy formed an outer layer of TiO 2 , believed to be at the expense of its oxidation resistance. 14,15 Cationic diffusion is inferred from the known transport mechanisms for Cr 2 O 3 growth 16,17 and from the fact that titanium must diffuse outwards to form above the outer scale.…”
Section: Classic Oxidationmentioning
confidence: 79%
“…[10][11][12][13][14] Energy-dispersive x-ray analyses showed that the overall oxide morphology from the external scale to internal oxides of Cr 2 O 3 /TiO 2 in the outer scale to Al 2 O 3 internally agrees with the expected thermodynamic behavior; however, and in contrast to the thermodynamic predictions, the alloy formed an outer layer of TiO 2 , believed to be at the expense of its oxidation resistance. 14,15 Cationic diffusion is inferred from the known transport mechanisms for Cr 2 O 3 growth 16,17 and from the fact that titanium must diffuse outwards to form above the outer scale.…”
Section: Classic Oxidationmentioning
confidence: 79%
“…[3][4][5][6] This is typical of Ni based superalloys used in rotor disc applications. 1,7,8,21 The alumina penetrations draw aluminium out of the c9 precipitates (Ni 3 Al) causing a c9 denuded zone to form ahead of the internally oxidised zone, this again penetrates into the alloy in two distinct penetrations (intergranular/intragranular) mirroring the internal oxide. 5,20 Previous studies on Udimet 720, ME3 and RR1000 have found that oxidation under cyclic fatigue or dwell fatigue conditions leads to an enhancement in the oxidation damage but the composition of the oxide was consistent with the un-stressed preexposed condition.…”
Section: Resultsmentioning
confidence: 99%
“…It could be the case that cracking of the intergranular internal oxide leads to a crack forming in both the external chromia scale and the sub-surface c/c9 alloy. Sudbrack et al 8 found that the carbide dissolution zone was the main cause of the high temperature fatigue life deficit in the Ni based superalloy, ME3, where weakened grain boundaries were thought to be the cause of initiation at high temperature. In the present case, the carbide dissolution zone is present appreciably beyond the crack and internal oxides ( Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations